อิทธิพลของการจัดการท่อนพันธุ์เนเปียร์ต่อการงอกของท่อนพันธุ์และผลผลิตของหญ้าเนเปียร์พันธุ์ปากช่อง 1 เพื่อใช้เป็นอาหารสัตว์ - ตัณมุขยกุล, นพ; ม่วงปั้น, จักรินทร์; โชติชุติมา, ทรงยศ; ทัดศรี, สายัณห์; สโรบล, เอ็จ (Thai Journal of Science and Technology, 2020)
This study aimed to determine influences of stem cutting pretreatment on stem cutting germination and grass dry matter yield of Napier grass cultivar Pakchong 1 for forage aspect. The experimental design was split plot design in Randomized complete block design with 4 replications. Main plot was how to keep the grass stem cutting cut to 4 types. Sub plot was how to plant the stem cutting cut to 3 patterns. The results showed that fresh stem cutting and the stem cutting kept in wet jute bag for 1 week, gave the germination at 83.33 and 78.33 percent, which were significantly higher (p < 0.05) than the stem cutting kept in transparent plastic bag for 2 weeks (50.83 percent). Moreover, the Napier grass from fresh stem cutting gave accumulated dry matter yield for 2 cycles of harvesting at 778.07 kg rai-1, which were higher (p < 0.05) than grass from storage in transparent plastic bag for 1 and 2 weeks stem cuttings that gave the accumulated dry matter yield at 591.66 and 515.46 kg rai-1. For accumulated protein yield, the grass from fresh stem cutting produced 98.22 kg protein rai-1 which was higher (p < 0.05) than the grass from storage transparent plastic bag for 1 and 2 weeks stem cuttings (73.09 and 62.84 kg protein rai-1). Meanwhile, the plant height, leaf stem ratio, hemicellulose, cellulose and lignin content were similar.